Gemarikan and Fishery Product Diversification Training as Effort of Reduce Stunting Prevalence - Hasti Detriani; Ikhsanul Khairi; Muhammad Rizal; Zuriat Zuriat; Hamidi Hamidi; Syarifah Zuraidah; Fazril Syahputra; Rudi Hermi; Nabila Ukhty; Anhar Rozi; Muhammad Faisi Ikhwali (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2023)
Stunting is a condition of failure to thrive in two-year-old babies due to chronic malnutrition. A short height characterizes babies experiencing stunting compared to other babies their age. One of the districts in Aceh Province with high stunting cases is Simuelue, with a prevalence reaching 35.7% in 2017. Various factors influence stunting, including nutrition and food quality. This service activity aims to increase public knowledge about the diversification of processed fish products and increase interest in eating fish, contributing to reducing stunting. The activity was carried out in two stages. The first is a campaign to enjoy eating fish using the socialization method. The campaign begins with socializing material about the benefits of eating fish, and introducing the types of fish. This activity ended with distributing processed fish meat products, namely nuggets. The second stage is the diversification of processing products using the workshop method. The workshop begins with explaining the steps for making a product, and then participants are divided into groups and make the product with their group. At each stage of the activity, a pre-test and post-test are given. The post-test results showed that understanding of product diversification and popularity increased after this activity.